FITERN: Firefighting Tactic and Technique Application as A Web-Based Learning Media Integrated with A Robotic Simulator - Nugraha, Wildan; Amalia, Direstu; Parjan, Parjan; Abdullah, Anton (JMKSP (Jurnal Manajemen, Kepemimpinan, dan Supervisi Pendidikan), 2023)
In the era of technological disruption and digital revolution, vocational higher education must align its graduates' competency and qualification needs and follow developments in science and technology in the workplace. Education is becoming increasingly complex, so it is necessary to implement new learning methods, one of which is e-learning-based education. This research aims to design and develop Fire Fighting Tactic and Technique Learning Media (FITERN) as a web-based learning media application product integrated with a robotic simulator. This research uses Research and Development (R&D) techniques with the ADDIE approach to ensure that information system development meets quality standards. The research results show that the feasibility assessment by media experts received an average score of 18.62 and a percentage of 93.12%, The feasibility assessment by material experts received an average score of 18.17 and a percentage of 90.83%, and Students' evaluation responses to FITERN learning media as seen from the aspects of programming (technical), media appearance (media presentation), material, and usefulness receive an average score of 18.62 and a percentage of 90.83%. So, the Development of The FITERN Application as A Web-Based Learning Media is proper for interactive multimedia learning. This research resulted in developing new and interactive learning media for firefighting tactics and techniques courses that utilize information technology and are integrated with firefighting robot systems so that students' learning outcomes can be further improved.